What Drives the Price of Solar Photovoltaic Electricity in Developing Countries? - Dobrotkova, Zuzana; Audinet, Pierre; Sargsyan, Gevorg (World Bank, Washington, DC, 2017)
This brief summarizes an analysis of 37 winning bids for utility-scale solar PV plants procured through auctions in 13 developing countries between 2013 and 2016. For comparison, the full report, obtainable from the authors, also describes examples of a failed PV auction in Indonesia and a large, bilaterally negotiated procurement of PV capacity in Nigeria. The 37 plants were selected based on the availability of plant-specific information and the desire to achieve a comprehensive overview of the evolution of auction results across countries and over time, in particular in countries such as Brazil and South Africa that have organized multiple rounds of auctions. The 37 plants were chosen from a set of some 500 winning bids covering more than 50 auctions in 16 countries. Although the sample is relatively small, it is large enough to explain the lowest announced prices and to indicate whether they are supported by market fundamentals. The analysis includes (i) a simple financial model (based on plant-specific parameters) that explains bidding prices and (ii) a comparison of auction designs in the countries covered, along with descriptions of the conditions under which individual auctions took place. Interviews with stakeholders active in utility-scale solar PV markets, including developers, utilities, consulting companies advising governments, bidders, government officials, and financial institutions, complement the analysis. Stakeholders verified some of the assumptions and conclusions, identified business strategies of market players, provided qualitative details about auction processes, and suggested avenues for bringing more sustainability into future solar PV development.